-3/4(x-3/4)=-3/8(x+3)

Simple and best practice solution for -3/4(x-3/4)=-3/8(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3/4(x-3/4)=-3/8(x+3) equation:


x in (-oo:+oo)

(-3/4)*(x-(3/4)) = (-3/8)*(x+3) // - (-3/8)*(x+3)

(-3/4)*(x-(3/4))-((-3/8)*(x+3)) = 0

(-3/4)*(x-3/4)+(3/8)*(x+3) = 0

3/8*(x+3)-3/4*(x-3/4) = 0

3/8*(x+3)-3/4*(x-3/4) = 0

27/16-3/8*x = 0

27/16-3/8*x = 0

27/16-3/8*x = 0 // - 27/16

-3/8*x = -27/16 // : -3/8

x = -27/16/(-3/8)

x = 9/2

x = 9/2

See similar equations:

| 27x=x^2 | | 4/7x+2/3x=13 | | x(3x+1)=30 | | f(t)=5t^2+4t | | 10(20m+11)= | | 4x-1+2x+x+3=30 | | -7(t+5)=21 | | 8/x=1/4-x | | (1/2)x^2-8=0 | | 8x+8x=7x | | 8x+14=10x+8 | | 3=14h+17 | | 8x+15=10x+8 | | 3x/8*4/7 | | 15/x=0.6 | | a-4/4-5(a-3)/10=3a+12/5 | | 2-3a=7-2(2a+4) | | 1/2*x^2-7x=0 | | 4x^6-37x^3+9=0 | | x+7/6=x+2 | | -14+3(x+10)=7(2x+5)+x | | 22y+3=12y | | x^8-7x^7-7x^6= | | 4(t-6)+8t=6(2t+5)-11 | | (3b^3-2b^2+b)(2b-3)= | | 5y^2-30y-135=0 | | 20c^2-17ct-63t^2=0 | | 3x+9=2(22-x) | | -u+3=2u+6 | | -11/9+1/2x-11/3x=3/2x-12/3-1 | | 15y-18y+1y=-2+40-2 | | 4(x-3)=x+15 |

Equations solver categories